Decree-Law of the President of the Arab Republic of Egypt No. 203 of the Year 2014 Regarding the Stimulation of Producing Electricity from Renewable Energy Sources = قرار رئيس جمهورية مصر العربية بالقانون رقم 203 لسنة 2014 بشأن تحفيز إنتاج الكهرباء من مصادر الطاقة المتجددة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic